2020
DOI: 10.1080/23322705.2020.1690116
|View full text |Cite
|
Sign up to set email alerts
|

Transgender People and Human Trafficking: Intersectional Exclusion of Transgender Migrants and People of Color from Anti-trafficking Protection in the United States

Abstract: Transgender (hereafter: trans) people are rarely included in human trafficking research. This empirical study presents narratives of trans individuals who report experiences consistent with the Palermo Protocol's definition of trafficking, access to anti-trafficking services for trans individuals, and attitudes of antitrafficking advocates and law enforcement toward trans people. Ethnographic fieldwork conducted for 30 months between March 2017 and August 2019 in Los Angeles and New York City included in-depth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Bernstein (2010) coined carceral feminism , a term initially referring to the neo-abolitionist feminist activism built on the reliance on, and commitment to, punitive strategies (e.g., criminalization and incarceration) to solve sex trafficking and now expanding to critiquing different forms of feminist anti-violence work that collaborates with multiple carceral systems, such as police, courts, and correctional institutions (Kim, 2018). The carceral intervention paradigm against sex trafficking has not only directed increasing attention and resources to criminalizing parities in the sex industry but also, in reality, exposed sex workers and those profiled as involved in sex work (often people of color, migrant women, and/or sexual minorities) to increased policing and surveillance (Dank et al, 2017; Fehrenbacher et al, 2020; Global Health Justice Partnership, 2018; Kaye, 2017; Pickering & Ham, 2013). For instance, under the Trump Administration, in 2017, Public Law 115–164 (commonly referred to as FOSTA-SESTA), was signed by the then-President; while the bills intend to fight against “online sex trafficking,” they in fact impose criminal penalties on websites that allow sex workers to advertise online, making the workplaces of sex workers more dangerous, sending potential trafficking even more underground, and creating more barriers to conducting online rights activism among sex workers and activists (Blunt et al, 2020; Blunt & Wolf, 2020; Chamberlain, 2019; Russo, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Bernstein (2010) coined carceral feminism , a term initially referring to the neo-abolitionist feminist activism built on the reliance on, and commitment to, punitive strategies (e.g., criminalization and incarceration) to solve sex trafficking and now expanding to critiquing different forms of feminist anti-violence work that collaborates with multiple carceral systems, such as police, courts, and correctional institutions (Kim, 2018). The carceral intervention paradigm against sex trafficking has not only directed increasing attention and resources to criminalizing parities in the sex industry but also, in reality, exposed sex workers and those profiled as involved in sex work (often people of color, migrant women, and/or sexual minorities) to increased policing and surveillance (Dank et al, 2017; Fehrenbacher et al, 2020; Global Health Justice Partnership, 2018; Kaye, 2017; Pickering & Ham, 2013). For instance, under the Trump Administration, in 2017, Public Law 115–164 (commonly referred to as FOSTA-SESTA), was signed by the then-President; while the bills intend to fight against “online sex trafficking,” they in fact impose criminal penalties on websites that allow sex workers to advertise online, making the workplaces of sex workers more dangerous, sending potential trafficking even more underground, and creating more barriers to conducting online rights activism among sex workers and activists (Blunt et al, 2020; Blunt & Wolf, 2020; Chamberlain, 2019; Russo, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…We acknowledge that not all pregnant and birthing persons identify as their gender assigned at birth. There is other existing research that addresses the ways in which border policies impact people who identify as non-binary, gender non-conforming, transgender, and/or Queer in similar and complicated ways (Fehrenbacher et al, 2020 ; Hubach et al, 2022 ; Jones, 2021 ). However, the case studies used in this policy analysis represent pregnant and birthing persons who are identified as female.…”
Section: Reproductive Justicementioning
confidence: 99%
“…Though framed in assistive terms, the effects of this kind of "carceral protection" carries collateral consequences, such as a criminal record that limits employment, housing, and educational opportunities (Musto 2016). Notably, cisgender and transgender women and people of color endure the bluntest force of punitive efforts pitched as protective (Fehrenbacher et al 2020).…”
Section: Introductionmentioning
confidence: 99%